2017
DOI: 10.4049/jimmunol.1600602
|View full text |Cite
|
Sign up to set email alerts
|

Human Lung Fibroblasts Present Bacterial Antigens to Autologous Lung Th Cells

Abstract: Lung fibroblasts are key structural cells that reside in the submucosa where they are in contact with large numbers of CD4 Th cells. During severe viral infection and chronic inflammation, the submucosa is susceptible to bacterial invasion by lung microbiota such as nontypeable Haemophilus influenzae (NTHi). Given their proximity in tissue, we hypothesized that human lung fibroblasts play an important role in modulating Th cell responses to NTHi. We demonstrate that fibroblasts express the critical CD4 T cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 55 publications
(66 reference statements)
4
18
0
Order By: Relevance
“…Th1>Th17>T-regulatory (Treg) cells>Th2. 56 Additionally, this work confirmed that naive cells are rare within the peripheral lung environment and that CD45RO+CCR7-effector memory cells predominated, making up approximately 80% of T cells found in the lung, with the majority of the remainder being central memory cells. 7,56,57 An important difference between naïve and memory T cells is their requirement for costimulatory signals.…”
Section: Fibroblast Innate Immunological Functionssupporting
confidence: 66%
See 3 more Smart Citations
“…Th1>Th17>T-regulatory (Treg) cells>Th2. 56 Additionally, this work confirmed that naive cells are rare within the peripheral lung environment and that CD45RO+CCR7-effector memory cells predominated, making up approximately 80% of T cells found in the lung, with the majority of the remainder being central memory cells. 7,56,57 An important difference between naïve and memory T cells is their requirement for costimulatory signals.…”
Section: Fibroblast Innate Immunological Functionssupporting
confidence: 66%
“…56 Additionally, this work confirmed that naive cells are rare within the peripheral lung environment and that CD45RO+CCR7-effector memory cells predominated, making up approximately 80% of T cells found in the lung, with the majority of the remainder being central memory cells. 7,56,57 An important difference between naïve and memory T cells is their requirement for costimulatory signals. While naïve T cells are recognised as having an absolute requirement for signalling through CD28-CD80/86 interaction, it has been shown that memory T cell populations do not necessarily require this interaction to reactivate.…”
Section: Fibroblast Innate Immunological Functionssupporting
confidence: 66%
See 2 more Smart Citations
“…Primary human lung fibroblasts were isolated by explant outgrowth from fresh or cryopreserved tumor-free tissue derived from distal airway-free lung tissue (parenchymal fibroblasts) or from small airways (peribronchial fibroblasts) following published protocols 25,52-54 . Cells were collected from several explant pieces to preserve heterogeneity HLF were maintained in 2% FBS DMEM ++ ( Table S3 ) and used within passages 2-4.…”
Section: Methodsmentioning
confidence: 99%